1989
DOI: 10.1139/z89-366
|View full text |Cite
|
Sign up to set email alerts
|

Populations of ferruginous and Swainson's hawks increase in synchrony with ground squirrels

Abstract: We compared changes in the densities of breeding ferruginous (Buteo regalis) and Swainson's hawks (Buteo swainsoni) over a period of 9 years with the abundance of a major prey species, Richardson's ground squirrel (Spermophilus richardsonii). We used the amount of poison distributed by landowners annually in their attempts to reduce crop damage by ground squirrels as an index of ground squirrel abundance. Though ground squirrel abundance was positively correlated with hawk density overall, the hawks differed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
(38 reference statements)
0
30
2
Order By: Relevance
“…Declines in ferruginous hawk numbers in certain parts of its range and concomitant increases in other areas suggest that ferruginous hawks adapt to local fluctuations in prey populations. Abundance of breeding pairs of ferruginous hawks has been significantly correlated with abundance of prey populations in central Utah Murphy 1978, Woffinden andMurphy 1989), Alberta (Schmutz and Hungle 1989), and New Mexico (Cook et al 2003). In addition, a decline in abundance of migrating and wintering ferruginous hawks was correlated with loss of prairie dogs in Colorado and New Mexico (Cully 1991, Seery andMatiatos 2000).…”
Section: Population Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…Declines in ferruginous hawk numbers in certain parts of its range and concomitant increases in other areas suggest that ferruginous hawks adapt to local fluctuations in prey populations. Abundance of breeding pairs of ferruginous hawks has been significantly correlated with abundance of prey populations in central Utah Murphy 1978, Woffinden andMurphy 1989), Alberta (Schmutz and Hungle 1989), and New Mexico (Cook et al 2003). In addition, a decline in abundance of migrating and wintering ferruginous hawks was correlated with loss of prairie dogs in Colorado and New Mexico (Cully 1991, Seery andMatiatos 2000).…”
Section: Population Trendsmentioning
confidence: 99%
“…Ferruginous hawk productivity is closely tied to the density of major prey items (Stalmaster 1988, Schmutz and Hungle 1989, Woffinden and Murphy 1989, Cook et al 2003. Several researchers have reported strong correlations between jackrabbit abundance and ferruginous hawk productivity (Smith and Murphy 1979, Thurow et al 1980, White and Thurow 1985, Woffinden and Murphy 1989, or ground squirrel/prairie dog abundance and ferruginous hawk productivity (Steehnof and Kochert 1985, Schmutz and Hungle 1989, Schmutz 1991, Cook et al 2003.…”
Section: Factors Affecting Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In Alberta, Downey et al (2003) found a positive correlation between Ferruginous Hawk numbers and densities of ground squirrels. Although historical data on ground squirrels in Alberta is limited, based on sales of poison used by farmers for ground squirrels (Schmutz and Hungle 1989) it is believed that ground squirrel numbers were high during the late 1980s and early 1990s. Nesting densities around Hanna, AB rose slightly from 10.3±0.5SE per 100 km 2 in 1975-77 to 13.5±0.2 in 1986-90, then declined sharply to 4.4±0.6 in 2001-06 ( Fig.…”
Section: )mentioning
confidence: 99%
“…Only entrances that were well opened and without collapsed dirt or vegetation growing in the entrance were counted (Schmutz and Hungle 1989;Finger et al 2007*). Therefore, for each study plot, we tallied burrow entrances along a transect 280 m in length.…”
Section: Distribution Of Richardson's Ground Squirrels According To Smentioning
confidence: 99%